Hubungan Pengetahuan dan Sikap Siswa Kelas v SD terhadap Perilaku Cuci Tangan Pakai Sabun (CTPS) di SD Negeri 097319 Siopat Suhu Kabupaten Simalungun tahun 2019 - Sri Rahma Friani (Maternal & Neonatal Health Journal, 2020)
Washing hands with soap is one of the most effective ways to prevent diarrhea and ARI, both of which are the main causes of child mortality. Every year, as many as 3.5 million children worldwide die before reaching the age of five because of diarrhea and ARI. Washing hands with soap can also prevent skin, eye, worms and bird flu infections. The importance of cultivating washing hands with soap properly and correctly is also supported by the World Health Organization (WHO). WHO data shows that every year an average of 100,000 children in Indonesia die from diarrhea. The purpose of this study was to determine the relationship between knowledge and attitudes of fifth grade elementary school students on the behavior of washing hands with soap. This type of research is analytical. The population of this study were all fifth grade students of SD Negeri 097319 Siopat Suhu Simalungun Regency in 2019. The sample in the study was 38 people. The results of the study were obtained based on knowledge, it is known that out of 38 students, the majority of respondents have less knowledge on the behavior of not doing ctps as many as 18 respondents (85.7%) and based on the attitude it is known that of the 38 students the majority of respondents have a lack of behavior on not doing ctps as many as 16 respondents (88 , 9%). It is hoped that this research can be an input for teaching staff and health workers to improve the quality of health services and education as well as information about Hand Washing with Soap by providing counseling.